From Soma To Psyche: An Outcome Evaluation Of Psychodynamic Psychotherapy In A Patient With Somatic Symptoms And Chronic Diseases. (29th January 2020) - Laskoski, Pricilla Braga; Serralta, Fernanda Barcellos; Barros, Alcina Juliana Soares; Teche, Stefania Pigatto; Hauck, Simone; Eizirik, Cláudio Laks
Abstract : This paper presents and discusses the outcomes of the psychodynamic psychotherapy of a patient with somatic symptom disorder and chronic diseases in a naturalistic setting. The entire treatment included 120 weekly sessions and lasted 30 months. It was interrupted by the patient. The treatment was considered successful in terms of its results. Regarding symptomatic evaluation (assessed by Outcome Questionnaire, OQ‐45), the patient showed an improvement, especially during the three‐month follow‐up assessment period, showing a change from dysfunction to functionality. In relation to personality evaluation (assessed by the Shedler‐Westen Assessment Procedure, SWAP‐200), although structural changes were not completed, the patient achieved a high level of overall functioning (i.e. strengthening of the ego). The clinical evaluation and the measures provided by the instruments were in agreement. This study showed that psychodynamic psychotherapy can help patients who show characteristics such as chronic diseases and operative functioning. Moreover, the pluralistic perspective used for evaluating treatment outcome proved to be very hopeful for improving our understanding of the patient's idiosyncrasies.